2022
DOI: 10.1177/00033197221124776
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epicardial Fat Volume with Coronary Artery Ectasia and Coronary Artery Disease

Abstract: Epicardial fat may play an important role in the pathogenesis of coronary artery disease (CAD). We investigated the relationship between coronary artery ectasia (CAE) and epicardial fat volume (EFV). This retrospective study included 506 patients with CAE (group 1), 500 with CAD (group 2), and 500 patients with normal coronaries as controls (group 3). The pericardium was traced manually from the edge of the pulmonary trunk to the last measured by computed tomography slice containing images of the heart to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…3 Not only did Subhan et al strengthen the observation by Çetin et al 2 but they also included a large population (n = 500) of CAD patients. 1 A recently published meta-analysis (21 studies encompassing 4975 patients) underscored that greater EAT volume and thickness was associated with increasing CAD severity, regardless of imaging modality used (CCT or TTE). 4 Furthermore, impaired adipokine secretion, such as increased resistin 5 and decreased adiponectin release, 6,7 has also been suggested in CAE cases compared with healthy controls, while the role of EAT-mediated inflammation is highly suspected in the etiopathogenesis of the disease.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…3 Not only did Subhan et al strengthen the observation by Çetin et al 2 but they also included a large population (n = 500) of CAD patients. 1 A recently published meta-analysis (21 studies encompassing 4975 patients) underscored that greater EAT volume and thickness was associated with increasing CAD severity, regardless of imaging modality used (CCT or TTE). 4 Furthermore, impaired adipokine secretion, such as increased resistin 5 and decreased adiponectin release, 6,7 has also been suggested in CAE cases compared with healthy controls, while the role of EAT-mediated inflammation is highly suspected in the etiopathogenesis of the disease.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with interest the study by Subhan et al 1 investigating the association between epicardial adipose tissue (EAT) and isolated coronary artery ectasia (iCAE). They found that epicardial fat volume, as assessed by cardiac computed tomography (CCT), independently predicted iCAE and coronary artery disease (CAD).…”
mentioning
confidence: 99%
See 1 more Smart Citation